Recommendations for Management of Whiteflies, Whitefly-Transmitted Viruses, and Insecticide Resistance for Production of Cucurbit Crops in Florida: ENY-478/IN871, rev. 7/2022 - Martini, Xavier; Paret, Mathews; Polston, Jane E.; Adkins, Scott; Roberts, Pamela; Nyoike, Teresia; Liburd, Oscar E. (EDIS, 2022)
This publication lists and describes common viruses spread in cucurbit crops by whiteflies. It includes strategies for managing whiteflies, most of them originally from a similar publication on managing whiteflies in tomatoes.